Retrospective analysis of IMA ligation level effects on nodal dissection and anastomosis in colorectal cancer - Daqing Cheng; Yunpeng Zhang; Qunjun Lin; Ming Xu; Jue Wang; Peng Sun; Bo Han (Scientific Reports)
Abstract This study compared the outcomes of high versus low inferior mesenteric artery (IMA) ligation in 380 patients undergoing surgery for rectal or sigmoid colon cancer, with intraoperative indocyanine green (ICG) fluorescence angiography used to assess anastomotic perfusion. The high ligation group demonstrated significantly greater lymph node yield (13 vs.12 p < 0.001) and was associated with more advanced T/N stages, while operative time was longer (218 ± 45 vs. 189 ± 38 min, p < 0.001). ICG navigation enabled objective blood supply evaluation, resulting in no ischemia-related anastomotic leaks and comparable overall complication rates (3.1% vs. 3.4%, p = 0.82). These findings highlight that high ligation improves oncologic resection completeness through extended lymphadenectomy, whereas ICG fluorescence technology enhances anastomotic safety by providing real-time perfusion assessment, offering a dual advantage in colorectal cancer surgery.